PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS NASABAH DENGAN KEPUASAN NASABAH SEBAGAI PEMEDIASI (Survei pada Nasabah Tabungan Tamades pada PD BKK Karanganyar Cabang Kebakkramat) - Mulyono, Rohwiyati & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
This research aims to analyses the role of customer satisfaction as mediatingvariable of the effect service quality on customer loyalty. This study using sample of100 customers who have savings bank account of Tamades product owned PD BKKin Karanganyar of the Kebakkramat Branchs. To test hypothesis using path analysis.The result shows that (1) service quality has significance effect on customer loyalty,so the hypothesis 1 accepted; (2) service quality has significance effect on customersatisfaction, so the hypothesis 2 accepted; (3) customer satisfaction has significanceeffect on customer loyalty, so the hypothesis 3 accepted; (4) effect of service qualityon customer loyalty mediated customer satisfaction, so the hypothesis 4 accepted.Keywords: service quality, customer satisfaction, customer loyalty